Figurationen der Alterität in Alfred Döblins Reise in Polen - Jacques Lajarrige (Recherches Germaniques)
In many ways, the travelogue Journey to Poland reveals Döblin’s ambiguous relationship to political and religious otherness and an approach to the Eastern Jewish world that, in changing ways, conjures up many antisemitic images and ideologies, without the reader always being able to make a clear distinction between the author’s intention and the intentionality of the literary text. From a phenomenological perspective, this paper discusses Döblin’s reflections on the cultural differences between Western and Eastern Jews as a “confrontation with otherness” (B. Waldenfels) and as an attempt to reconnect with his Jewish roots.